A novel early mobility bundle improves length of stay and rates of readmission among hospitalized general medicine patients. Issue 5 (2nd September 2020) - Bergbower, Emily Anne Smith; Herbst, Cole; Cheng, Nan; Aversano, Alexander; Pasqualini, Katherine; Hartline, Cierra; Hamby-Finkelstein, Devorah; Brewer, Colin; Benko, Stephen; Fuscaldo, Joseph
ABSTRACT: Inpatient early mobility initiatives are effective therapeutic interventions for improving patient outcomes and decreasing use of hospital resources among adult ICU and general medicine patients. To establish and demonstrate guidelines for early patient ambulation, we developed and implemented a novel multidisciplinary mobility bundle utilizing the JH-HLM (Johns Hopkins Highest Level of Mobility) scale for mobility classification, on a single adult general medicine unit of a community hospital. Our results show that patients admitted to the unit after implementation of the mobility bundle had improved mobility scores, reduced rates of 30-day hospital readmission, and a shortened length of hospital stay. This study emphasizes the importance of measuring mobility using a systematic method, easing workflow among unit practitioners, and allowing mobility initiatives to be jointly driven by nursing, physical therapy, and physicians.